Prevalence of myopia among children and adolescents aged 6–16 during COVID-19 pandemic: a large-scale cross-sectional study in Tianjin, China - Li, Tongtong; Wei, Ruihua; Du, Bei; Wu, Qi; Yan, Jing; Meng, Xiangda; Liu, Yuanyuan; Yang, Qiang; Kee, Chea-Su; Huang, Guowei; Yan, Hua (British journal of ophthalmology, 2024)
PurposeThis study aimed to determine the prevalence of myopia among children and adolescents aged 6–16 years during COVID-19 pandemic in Tianjin, China.MethodsThis was a cross-sectional study using data from the Tianjin Child and Adolescent Research of Eye between March and June in 2021. A total of 909 835 children and adolescents aged 6–16 years from 1348 primary and secondary schools in Tianjin, China were recruited. Prevalence of myopia with 95% CIs was described in different regions, sexes and ages. The regions-standardised prevalence rate and chain growth rate of myopia in different ages were described the characteristics of myopia.ResultsA total of 864 828 participants (95.05% participation rate) were included in the analysis. The age range was 6–16 with a mean age of 11.50±2.79 years. The overall prevalence of myopia was 54.71% (95% CI 54.60% to 54.81%). The prevalence of myopia was 57.58% (95% CI 57.43% to 57.73%) for girls and 52.05% (95% CI 51.91% to 52.20%) for boys. Students living in the six central districts had the highest prevalence of moderate myopia (19.09% (95% CI 19.01% to 19.17%)) and high myopia (5.43% (95% CI 5.39% to 5.48%)). The regions-standardised prevalence of myopia was increased by age and the highest chain growth rate of myopia was up to 47.99% at 8 years.ConclusionsThe prevalence of myopia in Tianjin is high during COVID-19 pandemic. The progression of myopia started to increase dramatically at 8 years, and the increasing slowed down at 14 years. For policy-makers, intervention in the lower age groups may be important to control myopia progression.